Quality of life patients after treatment of mandibular fractures with ORIF in oral surgery departement of Dr. Sardjito general hospital - Apriza, Edmond; Rahardjo, Rahardjo; Hasan, Cahya Yustisia (Faculty of Dentistry, Universitas Gadjah Mada, 2020)
Management of mandibular fracture using open reduction Internal fixation (ORIF) method is one of the ideal treatments for single and multiple mandibular fractures. The aim of this study was to determine the quality of life of patients after the treatment of mandibular fractures with ORIF using miniplate in single and multiple mandibular fractures. This research used case-control by recalling 43 research subjects in the oral surgery department Dr Sardjito general hospital between 2013 and 2017, that consisted of patients suffering from 23 single fractures and 20 multiple mandibular fractures. Each fracture would be examined clinically and subjectively. Clinical examination parameters were conducted using the mandibular mobility index (MMI) consisting of mouth opening assessment, left and right lateral mandibular excursion, and mandibular protrusive movement. Subjective parameters were performed based on general oral health asseesment index (GOHAI) questionnaire to assess physiological aspects, psychosocial aspects, and pain. The results of the chi-square test statistic study showed that the quality of life of a patient with a single mandibular fracture was better than that of multiple mandibular fractures based on MMI and GOHAI examinations. It was concluded that patients with a single mandibular fracture had a younger age, longer time adaptation and have a better quality of life.